Metaheurística Híbrida GRASP e Busca Tabu Aplicada ao Problema de Escalonamento de Tarefas - Cunha, Cláudia Rossana (2010)
This work approaches the problem of the tasks scheduling (Job Shop Scheduling) through the combination of the GRASP and Tabu Search metaheuristics. The study consists of using the GRASP (Greedy Randomized Adaptive Search Procedure) in the construction phase of the initial solution, suggesting for that, a specific procedure based on Coffman Gramah algorithm. However, such procedure was the great differential in this study, since it offers an initial solution qualitatively better, what allows the reduction of the local search time, where it was utilized the Tabu Search metaheuristic in the local search phase, which provided best results when it was compared with other metaheuristics that have the same structural base. The combination GRASP and Tabu Search were evaluated under two differentiated implementations, being one with Tabu Search in its form more simplified and another one with Tabu Search developing a process of optimized search, using an aditional mathematical model, which demonstrated great advancements in relation at processing time and the obtained results. The computational results, when compared with the existing ones in literature, they had shown that GRASP and Tabu Search combination are capable to produce good solutions.